2017
DOI: 10.1177/0003489417702923
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Response to Allogeneic Adipose Tissue-Derived Stromal Cells in Hyaluronan-Based Hydrogel in a Porcine Vocal Fold Injury Model

Abstract: The ASC-constructs were biocompatible; they did not influence the macrophage inflammatory response or provoke increases in collagen expression. Long-term engraftment was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Previous flow cytometry in pigs after VF injury also found no difference in macrophage phenotype at 3 or 7 days among hydrogel with allogeneic porcine ASC, hydrogel injection alone, and injured control. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous flow cytometry in pigs after VF injury also found no difference in macrophage phenotype at 3 or 7 days among hydrogel with allogeneic porcine ASC, hydrogel injection alone, and injured control. 23 …”
Section: Discussionmentioning
confidence: 99%
“…[38] Upon injury to the lamina propria, rapid neutrophil and monocyte recruitment from peripheral capillaries occurs, as demonstrated across experimental models of mice, [40] rats, [41][42][43][44] rabbits, [45] and pigs. [46,47] Li-Jessen's team applied multicolor flow cytometry to characterize temporal trajectories of neutrophils…”
Section: Immunological Profile Of the Vocal Foldsmentioning
confidence: 99%
“…For example, sourcing primary autologous (or even allogenic) vocal fold fibroblasts and epithelial cells is difficult due to the small size of the vocal folds and accessibility issues. [148,149] As such, other cell sources such as MSCs derived from bone marrow [150][151][152] or adipose [46,153] tissue and induced pluripotent stem cells (iPSCs) [154] have been sought for defected vocal fold treatments.…”
Section: Cell-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Valerie et al [96] showed that transplanting ASCs into a chronic scar could regenerate the VF by dissolving the excess collagen fibers that form the scar tissue and restoring the normal structure of elastic fibers. King et al [97] used ASCs embedded in a hyaluronan scaffold for VF scarring. These researchers investigated the macrophage inflammatory response to allogeneic ASCs and concluded that the constructs were biocompatible.…”
Section: New Strategies For Vf Scar Including Regenerative Medicinmentioning
confidence: 99%